Public Relation sebagai Wajah Utama Perbankan dalam Meningkatkan Kepercayaan Investor - Irawati, Indriana (Maliki Interdisciplinary Journal, 2025)
In an era of rapid and complex information, banking companies face significant challenges in building and maintaining investor confidence. PR acts as a communication bridge between the company and its stakeholders, and plays an important role in the company’s image. Transparency and effective communication are key to reducing distance and building a positive image. Through cooperation with the media, banks ensure that the information conveyed is accurate and supports a positive image. In the fierce competition of the banking industry, PR’s ability to build good relationships with investors is a determining factor in the company’s long-term success. Public relations (PR) plays a crucial role in fostering communication between a company and its various stakeholders, including investors, the media, and the public. Effective PR can help banks provide clear and consistent information about their operations, performance, and initiatives, reducing risk and increasing profitability.